Microarray analysis of normal and abnormal chick ventricular myocardial development - Krejčí, E; Pesevski, Z; DeAlmeida, A C; Mrug, M; Fresco, V M; Argraves, W S; Barth, J L; Cui, X; Sedmera, D (Physiological research, 2012)
The left and right ventricle originate from distinct parts of the cardiac tube, and several genes are known to be differentially expressed in these compartments. The aims of this study were to determine developmental differences in gene expression between the left and right ventricle, and to assess the effect of altered hemodynamic loading. RNA was extracted from isolated left and right normal chick embryonic ventricles at embryonic day 6, 8, and 10, and from day 8 left atrial ligated hearts with hypoplastic left and dilated right ventricles. cRNA was hybridized to Affymetrix Chicken Genome array according to manufacturer protocols. Microarray analysis identified 302 transcripts that were differentially expressed between the left and right ventricle. Comparative analysis detected 91 genes that were different in left ventricles of ligated hearts compared to age-matched ventricles, while 66 were different in the right ones. A large number of the changes could be interpreted as a delay of normal maturation. The approach described in this study could be used as one of the measures to gauge success of surgical procedures for congenital heart disease and help in determining the optimal time frame for intervention to prevent onset of irreversible changes.
Keywords: srdeční síně; Chick Embryo; Heart Ventricles; Microarray Analysis; Transcriptome; myokard; Animals; hemodynamika; mikročipová analýza; Myocardium; Hemodynamics; zvířata; srdeční komory; Heart Atria; transkriptom; kuřecí embryo